Effect of microstructure evolution during plastic deformation on the formability of Transformation Induced Plasticity and Quenched & Partitioned AHSS. (15th August 2018) - Bhargava, Marrapu; Chakrabarty, Shanta; Barnwal, Vivek Kumar; Tewari, Asim; Mishra, Sushil K.
Abstract: The effect of strain path on the microstructure evolution of two different advanced high strength steel alloys (AHSS alloys) has been studied in this work. The two AHSS alloys considered are Transformation Induced Plasticity (TRIP) and Quenched and Partitioned (Q&P) steels. The formability of these AHSS was calculated at different strain paths using limit dome height (LDH) tests. Both of these AHSS show unusual formability behavior at the stretching region of the Forming Limit Diagram (FLD). A comprehensive microstructure and texture study was performed at different strain levels and near the principal strain paths to understand the effect of microstructure on the formability of these AHSS. This study clearly highlights the significance of development of α and γ fibre texture, at different strain paths, affecting the formability of AHSS steels. Additionally, the evolution of other microstructure and crystallographic texture features such as phase transformation, misorientation development, texture intensity and Taylor's factor also affect the formability of these AHSS. It has also been observed that γ fibre, maximum orientation distribution (ODF), texture intensity and misorientations are reduced in the stretching region and decrease the formability of these AHSS. Graphical abstract: Unlabelled Image Highlights: The forming behaviour of two different advanced high strength steels (AHSS), TRIP and Q&P steels, was studied. Both the steels, TRIP and Q&P, show an unusual sharp decline in formability at biaxial strain path. The reduction in γ fibre fraction during deformation is the main reason for this drop in formability for both the steels. The evolution of various other microstructure characteristics is correlated with the formability of the steels.